Small interfering RNA delivery into the liver by cationic cholesterol derivative-based liposomes. (2nd October 2017) - Hattori, Yoshiyuki; Machida, Yoko; Honda, Maho; Takeuchi, Nozomi; Yoshiike, Yuki; Ohno, Hiroaki; Onishi, Hiraku
Abstract: Purpose : Previously, we reported that the cationic liposomes composed of a cationic cholesterol derivative, cholesteryl (2-((2-hydroxyethyl)amino)ethyl)carbamate (OH-C-Chol) and 1, 2-dioleoyl- sn -glycero-3-phosphoethanolamine (DOPE) (termed LP-C), could deliver small interfering RNAs (siRNAs) with high transfection efficiency into tumor cells. In this study, to develop a liposomal vector for siRNA delivery in vivo, we prepared the poly(ethyleneglycol) (PEG)-modified cationic liposomes (LP-C-PEG) and evaluated their transfection efficiency in vitro and in vivo . Materials and methods : We prepared LP-C-PEG/siRNA complexes (LP-C-PEG lipoplexes) formed in water or 50 mM NaCl solution, and evaluated their siRNA biodistribution and gene silencing effect in mice after intravenous injection. Results : LP-C-PEG lipoplexes strongly exhibited in vitro gene silencing effects in human breast tumor MCF-7 cells as well as LP-C lipoplexes. In particular, formation of LP-C and LP-C-PEG lipoplexes in the NaCl solution increased the cellular association. When LP-C-PEG lipoplexes with Cy5.5-labeled siRNA formed in water or NaCl solution were injected into mice, accumulation of the siRNA was observed in the liver. Furthermore, injection of LP-C-PEG lipoplexes with ApoB siRNA could suppress ApoB mRNA levels in the liver and reduce very-low-density lipoprotein/low-density lipoprotein levels in serum compared with that after Cont siRNA transfection, although the presence of NaCl solution in forming the lipoplexes did not affect gene silencing effects in vivo . Conclusions : LP-C-PEG may have potential as a gene vector for siRNA delivery to the liver.